2010
DOI: 10.1074/jbc.m109.096032
|View full text |Cite
|
Sign up to set email alerts
|

Her4 and Her2/neu Tyrosine Kinase Domains Dimerize and Activate in a Reconstituted in Vitro System

Abstract: Her4 (ErbB-4) and Her2/neu (ErbB-2) are receptor-tyrosine kinases belonging to the epidermal growth factor receptor (EGFR) family. Crystal structures of EGFR and Her4 kinase domains demonstrate kinase dimerization and activation through an allosteric mechanism. The kinase domains form an asymmetric dimer, where the C-lobe surface of one monomer contacts the N-lobe of the other monomer. EGFR kinase dimerization and activation in vitro was previously reported using a nickel-chelating lipid-liposome system, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 47 publications
3
73
0
Order By: Relevance
“…Liposomes-Liposomes were prepared and used essentially as described (41,42). Briefly, Ni 2ϩ -NTA-DOGS and DOPC in chloroform were mixed at the desired ratio in 1 mg of total lipid and dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes-Liposomes were prepared and used essentially as described (41,42). Briefly, Ni 2ϩ -NTA-DOGS and DOPC in chloroform were mixed at the desired ratio in 1 mg of total lipid and dried under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Extruded liposomes were stored at 4°C prior to use. Surface area calculations used to estimate the effective protein concentration on the liposome surface were as described (41,42).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HER3 forms heterodimers with EGFR, resulting in activation despite the absence of a known active kinase domain (8). Several studies have shown that these heterodimerizations within the EGFR family are accelerated by receptor-specific ligands such as EGF or heregulins (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although a substantial body of evidence supports this model for EGF receptor kinase activation (9)(10)(11)13), it is not clear how the binding of ligand to the extracellular domain directs the assembly of the intracellular asymmetric kinase dimer. In particular, if ligand binds to one subunit in an ErbB dimer, which kinase domain adopts the activator and which adopts the receiver position in the asymmetric dimer, or is the choice made randomly?…”
mentioning
confidence: 99%